2017
DOI: 10.3390/en10020216
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Electric Vehicle Powertrain System Supporting Multi-Path Power Flows: Its Architecture, Parameter Determination and System Simulation

Abstract: Abstract:In this paper, a novel electric vehicle powertrain system is proposed. In the system, a coaxial magnetic gear (CMG), an electromagnetic clutch, a lock, and two electric machines (EMs) are adopted to achieve the power-split by controlling the states of the clutch and the lock, which enables electric vehicles (EVs) to work in four operation modes. The configuration, power flow paths and operation modes are depicted in detail. A dynamic model is established to help determine the parameters and build simu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Interested readers are referred to [24][25][26] for in-depth knowledge on the control and modeling of electric motor for EVs. While some research can be found with more than one electric motor as the propulsion device in EVs [27,28], a single electric motor is considered in this study as the propulsion device. Table 4 shows the motor capacity that is collected from a published article by Zhu et al [8].…”
Section: Electric Motormentioning
confidence: 99%
“…Interested readers are referred to [24][25][26] for in-depth knowledge on the control and modeling of electric motor for EVs. While some research can be found with more than one electric motor as the propulsion device in EVs [27,28], a single electric motor is considered in this study as the propulsion device. Table 4 shows the motor capacity that is collected from a published article by Zhu et al [8].…”
Section: Electric Motormentioning
confidence: 99%